Personal Health Records: Evaluation of Functionality and Utility - Kim, Matthew I. (American Medical Informatics Association, 2002)
Objectives: Web-based applications have been developed that allow patients to enter their own information into secure personal health records. These applications are being promoted as a means of providing patients and providers with universal access to updated medical information. The authors evaluated the functionality and utility of a selection of personal health records. Design: A targeted search strategy was used to identify eleven Web sites promoting different personal health records. Specific criteria related to the entry and display of data elements were developed to evaluate the functionality of each PHR. Information abstracted from an actual case was used to create a series of representative PHRs. Output generated for review was evaluated to assess the accuracy and completeness of clinical information related to the diagnosis and treatment of specific disorders. Results: The PHRs selected for review employed data entry methods that limited the range and content of patient-entered information related to medical history, medications, laboratory tests, diagnostic studies, and immunizations. Representative PHRs created with information abstracted from an actual case displayed varying amounts of information at basic and comprehensive levels of representation. Conclusions: Currently available PHRs demonstrate limited functionality. The data entry, validation, and information display methods they employ may limit their utility as representations of medical information.